Effects of Cerrado restoration on seasonal soil hydrological properties and insights on impacts of deforestation and climate change scenarios - Pereira, Luara Castilho; Balbinot, Leonardo; Nnadi, Ernest O.; Mosleh, Mojan Hadi; Tonello, Kelly Cristina (Frontiers in Forests and Global Change, 2022)
Knowing soil indicators during forest restoration is essentially better for understanding the recovery of ecosystem functions for water conservation. The aim of this study is to assess seasonal changes in hydrological properties of sandy soils subjected to passive restoration over 8 (F8), 11 (F11), and 46 (F46) years in the Cerrado. The soils assessed herein have the same land use history and climate conditions. Soil density (SD), moisture (SM), organic matter (SOM), resistance to penetration (SRP), infiltration rate (IR), and soil conductivity (K) were measured for 12 months, and a repellency index (RI) was obtained in the dry season. Some annual soil hydrological property differences based on passive restoration sites were observed, but differences in other properties were only noticed through seasonal analyses. Higher SM, IR, and K values were recorded in the rainy season, and higher SRP values were observed in the dry season. IR was approximately fourfold higher in F8 and threefold higher in F11 and F46 in the rainy season than in the dry season. IR was higher in the oldest restoration site and lower (by over 60%) in the youngest restoration site, which also showed higher RI. Thus, significant differences in several hydrological soil properties and forest restoration soils subjected to the assessed chrono-sequence helped to confirm the study hypothesis, namely: these properties are influenced by forest age and are a warning against deforestation and climate change scenarios. The recovery of hydrological properties can be a slow process, much slower than deforestation, and this can have severe implications because soil water inflow is related to groundwater maintenance. Therefore, improvement of hydrological properties can help to develop sustainable land management and better and more efficient soil conservation strategies for sites undergoing passive restoration such as the Cerrado.